The effect of short-term muscle vibration on knee joint torque and muscle firing patterns during a maximal voluntary isometric contraction - Lee, J.; Song, J.; Ahn, J.; Park, J. (Korean Journal of Sport Biomechanics, 2017)
Objective: To investigate the effect of short-term vibration frequencies on muscle force generation capabilities. Method: Six healthy participants were recruited for this study and only their dominant leg was tested. The subjects were tested under five conditions of vibration frequencies with constant amplitude: 0 Hz (no vibration), 30 Hz, 60 Hz, and 90 Hz, and the vibration amplitude was 10 mm for all frequency conditions. The vibration was applied to the rectus femoris (RF). The subjects were then instructed to maintain a steady-state isometric knee joint torque (100 Nm) for the first 6 s. After the steady-state torque production, the subjects were required to produce isometric knee joint torque by leg extension as hard as possible with a start signal within the next 3 s. The vibration was applied for ~4 s starting from 1 s before initiation of the change in the steady-state knee joint torque. Results: The results showed that the maximum voluntary torque (MVT) of the knee joint increased with the vibration frequencies. On average, the MVTs were 756.47 Nm for 0 Hz (no vibration) and 809.61 Nm for 90 Hz. There was a significant positive correlation (r = 0.71) between the MVTs and integrated electromyograms (iEMGs). Further, the co-contraction indices (CCIs) were computed, which represent the ratio of the iEMGs of the antagonist muscle to the iEMGs of all involved muscles. There was a significant negative correlation (r = 0.62) between the CCIs and MVTs, which was accompanied by a significant positive correlation (r = 0.69) between the iEMGs of the vibrated muscle (RF). There was no significant correlation between the MVTs and iEMGs of the antagonist muscle. Conclusion: The results of this study suggest that the short-term vibration on the muscle increases the level of muscle activation possibly owing to the increased Ia afferent activities, which enhances the muscle force generation capability.